2021
DOI: 10.7554/elife.69740
|View full text |Cite
|
Sign up to set email alerts
|

Functional independence of endogenous μ- and δ-opioid receptors co-expressed in cholinergic interneurons

Abstract: Learning to be safe is central for adaptive behaviour when threats are no longer present. Detecting the absence of an expected threat is key for threat extinction learning and an essential process for the behavioural treatment of anxiety related disorders. One possible mechanism underlying extinction learning is a dopaminergic mismatch signal that encodes the absence of an expected threat. Here we show that such a dopamine-related pathway underlies extinction learning in humans. Dopaminergic enhancement via ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“… (C) Agonist-dependent endocytosis of endogenous MOR and DOR in striatal cholinergic interneurons. 2 Arrow heads indicate fluorescence staining along plasma membrane, which appears as a line. Arrows show some pools of endosomes as fluorescence puncta throughout the cytoplasm after agonist activation.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“… (C) Agonist-dependent endocytosis of endogenous MOR and DOR in striatal cholinergic interneurons. 2 Arrow heads indicate fluorescence staining along plasma membrane, which appears as a line. Arrows show some pools of endosomes as fluorescence puncta throughout the cytoplasm after agonist activation.…”
Section: Step-by-step Methods Detailsmentioning
confidence: 99%
“… 3 The development of a chemical labeling approach that resulted in naltrexamine-acylimidazole compounds (NAIs) offers alternative ways to study endogenous ORs from any cells or animals. 1 , 2 The labeling of ORs with NAI compounds relies on a high affinity antagonist naltrexamine to initiate binding at the orthosteric pocket of receptor, which then guide a chemical bond to take place between the reactive acylimidazole moiety of NAI and a nucleophile of amino acid side chains including Lys, Ser, Thr, Tyr or His on the receptor ( Figure 1 A). The reaction yields a permanent attachment of a reporter or fluorescent dye to the receptor.…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that this first-of-kind approach could presumably be transposed to other GPCRs, the use of such probes might eventually be applied for the study of OPr. Similarly, although it was not carried out in living animals, advances have also been recently denoted for the visualization of endogenous MOPr and DOPr in striatal cholinergic interneurons (Arttamangkul et al, 2021). Using NAI-A594, a ligand-directed labeling agent, the authors fluorescently labeled both OPr from live brain slices and concluded that MOPr and DOPr function independently, despite being localized in the same neurons (Arttamangkul et al, 2021).…”
Section: Knock-in Mouse Lines Harboring a G Protein-coupled Receptors-fluorescent Protein Fusionmentioning
confidence: 99%